Identification of Pathogen Protozoans (Cryptosporidium spp and Giardia lamblia) from Canteen’s Water-sources at Jatinangor, West Java, Indonesia - Komathi Nair Murugesan; Ridad Agoes; Sri Yusnita Irda Sari (Althea Medical Journal, 2017)
Background: The prevalence of intestinal protozoan infection caused by Cryptosporidium spp and Giardia lamblia has been rapidly increasing in developing countries. Contamination of water-sources by intestinal protozoans can spread infection to humans when it is consumed without any specific treatment. Jatinangor is an educational area where many universities are located and many students live in this area. This study aimed to identify the presence of intestinal protozoa (Cryptosporidium spp and Giardia lamblia) in water-sources used by canteens at Jatinangor area to detect the magnitude of protozoans intestinal infections.Methods: A descriptive cross sectional study was carried out from August to September 2014. Raw water samples from reservoir tanks, water containers and tapwater were taken from all canteens located along the main road of Jatinangor. Samples were centrifuged and divided into two portions; two drops from the first test tube was stained with Lugol solution and observed by 2 observers under a light microscope for Giardia lamblia, and sediments from the second test tube was stained using acid fast staining then observed for Cryptosporidium spp under the light microscope. Results: Out of 50 samples, 26 were positive for parasites, of which 22 (44%) were contaminated by Cryptosporidium spp and 4 (8%) were contaminated by Giardia lamblia.Conclusions: Half of the raw water-sources in Jatinangor are contaminated by Cryptosporidium spp and Giardia lamblia. Proper water treatment should be implemented by the owners of the canteens before it is consumed as drinking water.